Patient experience established: One year later - Geoffrey Silvera; Jason Wolf (Patient Experience Journal, 2015)
Scholars and administrators have long dedicated themselves to centering healthcare conversations and debates on the experiences of patients and their families. Patient experience advocates view these experiences as critical to evaluations of healthcare quality. There have been a great multitude of important contributions, yet, for decades, these calls for patient-centric care experiences and healthcare systems have been confined to the fringes of disparate health policy and reform debates. This bygone reality created a diaspora of scholars and administrators dedicated to understanding, evaluating, and improving the patient experience. This article begins to explore a coalescing around patient experience research efforts citing where people have turned to find leading research and reinforcing the value for an emerging research home for patient experience found on the pages of Patient Experience Journal itself.